2017
DOI: 10.1007/s11356-017-8785-z
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative effect of selenium on inflammatory damage caused by lead via inhibiting inflammatory factors and heat shock proteins in chicken testes

Abstract: The aim of this study was to investigate ameliorative effect of selenium (Se) on lead (Pb)-induced inflammatory damage in chicken testes. One hundred eighty 7-day-old male chickens were randomly assigned into the control group, the Se group, the Pb group, and the Pb/Se group. Lead acetate was added in drinking water (350 mg/L Pb). Sodium selenite was added in the standard commercial diet (1 mg/kg Se). On the 30th, 60th, and 90th days of the experiment, 15 chickens of each group were euthanized. Inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Studies about alleviative effect of Se on Pb poisoning in chickens were focused on in vivo , such as cartilages about mRNA expression of GPx1, GPx2, GPx3, GPx4, Txnrd1, Txnrd2, Txnrd3, Dio1, Dio2, Dio3, SelT, SelK, SelS, SelH, SelM, SelU, SelI, SelO, Selpb, Sepp1, Sepx1, Sep15, and SPS2 [ 22 ]; kidneys about mitochondrial dynamics and protein expression of Bcl-2, p53, Bax, Cyt c, and Caspase-3 [ 23 ]; bursa of Fabricius about oxidative stress indicators and cytokines mRNA expression [ 24 ]; and testes about mRNA and protein expression of inflammatory factors and heat shock proteins [ 25 ], mRNA expression of heat shock proteins and GPx1, GPx2, GPx3, GPx4, Txnrd1, Txnrd2, Txnrd3, Dio1, Dio2, Dio3, SelT, SelK, SelS, SelH, SelM, SelU, SelI, SelO, Selpb, Selpn1, Sepp1, Sepx1, Sepw1, Sep15, and SPS2 [ 26 ]. However, little is known about alleviative effect of Se on Pb-caused apoptosis in bird nervous tissues in vivo and in vitro via mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Studies about alleviative effect of Se on Pb poisoning in chickens were focused on in vivo , such as cartilages about mRNA expression of GPx1, GPx2, GPx3, GPx4, Txnrd1, Txnrd2, Txnrd3, Dio1, Dio2, Dio3, SelT, SelK, SelS, SelH, SelM, SelU, SelI, SelO, Selpb, Sepp1, Sepx1, Sep15, and SPS2 [ 22 ]; kidneys about mitochondrial dynamics and protein expression of Bcl-2, p53, Bax, Cyt c, and Caspase-3 [ 23 ]; bursa of Fabricius about oxidative stress indicators and cytokines mRNA expression [ 24 ]; and testes about mRNA and protein expression of inflammatory factors and heat shock proteins [ 25 ], mRNA expression of heat shock proteins and GPx1, GPx2, GPx3, GPx4, Txnrd1, Txnrd2, Txnrd3, Dio1, Dio2, Dio3, SelT, SelK, SelS, SelH, SelM, SelU, SelI, SelO, Selpb, Selpn1, Sepp1, Sepx1, Sepw1, Sep15, and SPS2 [ 26 ]. However, little is known about alleviative effect of Se on Pb-caused apoptosis in bird nervous tissues in vivo and in vitro via mitochondrial pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Also in this case, Se supplementation alleviated those changes [31]. Likewise, mRNA expression of iNOS, NF-κB, COX-2, and TNF-α , NO content and Pb deposition was ameliorated via Se supplementation in the testes of chicken [67]. In the same way, the results of another study indicated that Se alleviated the changes caused by Pb exposure on Bcl-2 mRNA and protein expression, the increased NO content, the iNOS activity, the relative mRNA and the protein expression of iNOS, the ER-related genes, and caspase-3 and caspase-12 protein expression.…”
Section: Avian Transcriptome Response To Lead Toxicity and The Benmentioning
confidence: 99%
“…Wang et al showed that Se supplementation alleviates accumulation of Pb in testes of chicken [67]. Additionally, other studies demonstrated that Se alleviates Pb-induced oxidative stress.…”
Section: Avian Transcriptome Response To Lead Toxicity and The Benmentioning
confidence: 99%
“…As an antioxidant, it helps in maintaining intracellular redox balance. Our previous study found that Se could alleviate Pb-caused oxidative stress [17], heat shock response [18], and in ammatory damage [19] in chicken testes. In addition, recent studies reported that Se-yeast inhibited the initiation of autophagy and enhanced autophagic clearance in the brains of Alzheimer's disease mice [20].…”
Section: Introductionmentioning
confidence: 96%
“…reported that Se alleviated the increase of IL-4 and IL-12β mRNA expression and the decrease of IL-2 mRNA expression caused by Pb in chicken neutrophils[49]. In addition, Se can mitigate Pb-caused increase of HSPs and autophagy Wang et al (2017). found that Pb poisoning induced mRNA expression of HSP27, HSP40, HSP60, HSP70, and HSP90; and Se administration alleviated the above HSPs changes in chicken testes[19].…”
mentioning
confidence: 94%